Prevalence of sorghum ergot in India, Vietnam, Thailand and Myanmar - Tonapi, V.; Navi, S.; Wirojwattanakul, K.; Vinh, D.V.; Thein, M.M.; Bandyopadhyay, Ranajit; Varanavasiappan, S.; Tooley, P. (Informa UK Limited, 2006)
Ergot is a serious seed-limiting disease that restricts the global movement of seeds. The environmental conditions favorable for disease development, especially nonavailability of pollen due to low temperature and high humidity prone the sorghum spikelets to ergot attack. Since the disease has attained significance through its global spread in Australia and Americas in the last decade, understanding sorghum ergot diversity and prevalence across geographical regions becomes very much essential. Hence extensive on-farm disease surveys were conducted from August 1999 to April 2002 in India and from August to November 2002 in Vietnam, Thailand and Myanmar. During the survey, a total of 152 ergot samples from India, 24 ergot samples from Vietnam, Thailand and Myanmar were collected. Out of 24 ergot samples from South East Asia, two were from Vietnam, 18 were from Thailand and four were from Myanmar. In India both incidence and severity of sorghum ergot ranged between 0 and 100%. In Vietnam ergot incidence was in traces and severity ranged from 2 to 7%. In Thailand incidence was from trace to 80% and severity ranged from 2 to 100%. In Myanmar, incidence was from trace to 40% and severity in the range of 5 – 80%.